2013
DOI: 10.18378/rvads.v8i1.1982
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade diária da temperatura do solo: Um estudo de caso

Abstract: <!--[if gte mso 9]><xml> <o:OfficeDocumentSettings> <o:TargetScreenSize>800x600</o:TargetScreenSize> </o:OfficeDocumentSettings> </xml><![endif]--><!--[if gte mso 9]><xml> <w:WordDocument> <w:View>Normal</w:View> <w:Zoom>0</w:Zoom> <w:TrackMoves /> <w:TrackFormatting /> <w:HyphenationZone>21</w:HyphenationZone> <w:PunctuationKerning /> <w:ValidateAgainstSchemas /> <w:SaveIfXMLInvalid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…As estimativas da difusividade térmica do solo estão de acordo com aquelas obtidas em Rao et al (2005), Oliveira et al (2010), Danelichen e Biudes (2011), Diniz et al (2013e). No que diz respeito à camada-1, com base na análise das Tabelas 2 e 3, verifica-se que as mais elevadas magnitudes da difusividade térmica são aquelas oriundas do método do arco tangente.…”
Section: Resultsunclassified
“…As estimativas da difusividade térmica do solo estão de acordo com aquelas obtidas em Rao et al (2005), Oliveira et al (2010), Danelichen e Biudes (2011), Diniz et al (2013e). No que diz respeito à camada-1, com base na análise das Tabelas 2 e 3, verifica-se que as mais elevadas magnitudes da difusividade térmica são aquelas oriundas do método do arco tangente.…”
Section: Resultsunclassified
“…According to Diniz et al (2013), soil temperatures in regions close to the surface present greater variability than the others due to their greater ease in losing (nocturnal period) and gaining (daytime) heat during the daily cycles. Therefore, it can be concluded that the daily variability of soil temperatures is inversely related to depth (GASPARIM et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…A Figura-2 Diniz et al (2013a), o decréscimo das temperaturas observadas em seguida é conseqüência do decaimento da disponibilidade energética.…”
Section: Resultsunclassified